Analysis and Practice of the Smart Home Application Development Technology - Longjie Xu; Wenda Ying (Dianxin kexue)
The present situation of the smart home application development technology was analyzed and a smart home application developing technology solution based on intelligent Wi-Fi connection module was put forward.The key technologies of the solution were analyzed and the feasibility of smart home application development technology based on this solution was verified.